Nurse Champions as Change Agents for Bedside Handover Compliance: A Case Study - Aisyah Rohie; Andi Amalia Wildani; Hanny Handiyani; Lia Setyarini (STIKep PPNI Jawa Barat, 2026)
Background: Bedside handover is an essential element of effective nurse-to-nurse communication to ensure patient safety. A preliminary assessment at Hospital X, supported by previous literature, identified limited knowledge, heavy workloads, and the absence of evaluation and appreciation systems as key barriers to optimal bedside handover implementation. Objective: This study aimed to identify the implementation of the Nurse Champion role in improving nurses' compliance with bedside handover at Hospital X using Kurt Lewin's Three-Step Change Model (Unfreeze–Move–Refreeze). Methods: This case study was conducted in the medical-surgical inpatient unit of Hospital X from 8 September to 1 October 2025 using Kurt Lewin's Three-Step Change Model. Baseline observations were conducted from 8–14 September 2025, followed by semi-structured interviews with four Primary Nurses on 19 September 2025. The intervention included bedside handover socialization (24 and 26 September), appointment of a Nurse Champion (24 September), checklist-based monitoring integrated into the shift workflow (24–30 September), implementation of reminder stickers, and a reward program (1 October). Nurses' compliance with bedside handover was evaluated at the end of the intervention. Results: Following the intervention, compliance across the 9P bedside handover components varied. The highest compliance was observed for Plan and Partnership (98.76%) and Patient Comfort (92.28%), whereas Personal Hygiene and Environment showed the lowest compliance (26.44%), indicating that these aspects were less consistently addressed during bedside handover. Conclusion: Therefore, the implementation of Nurse Champions based on Kurt Lewin’s Change Model was associated to improved compliance with 9P bedside handover and fostered sustainable behavioural change through enhanced motivation, appreciation, and a collaborative work culture in nursing practice